Weights of speech verbs in the Syriac language - Anwyia, Yaqoob; Khalifa , Ammar (Al-Adab Journal, 2025)
The topic of "speech verbs" is one of the important topics in the semantic classifications of verbs in language. This is due to its importance in determining its meaning, connotation, and how it is used in different contexts. It is beneficial in understanding the subject matter of texts and interpreting them more deeply by analyzing the verbs used and understanding their connotations. Speech verbs form a field of semantic fields classified by linguists in the science of semantics. Therefore, our study aims to collect speech verbs semantic field classified by linguists.This study aims to collect speech verbs (a single category) in the Syriac language from the lexicon of the late distinguished scholar, Bishop Mar Jacob Eugene Manna (Chaldean-Arabic), and classify them semantically according to semantic theories, and compare them with other Semitic languages. The key findings of our study can be summarized as follows:This research is divided into three main chapters:The first chapter is "Speech Verbs and their Structure in the Syriac Language," which is divided into two sections. The first section, "Grammatical Classifications of Speech Verbs," classifies speech verbs in the Syriac language according to grammatical categories such as regular and irregular verbs, transitive and intransitive verbs, etc. The second section, "Weights of Speech Verbs," discusses the verbal weights of speech verbs with examples.The second chapter, "Semantics of Speech Verbs," is also divided into two main sections. The first section, "Types of Semantics," discusses the most important semantic theories. The second section talks about the theory of semantic fields, with a general classification of verbs in the Syriac language and a specific focus on the class of speech verbsj.The practical and applied aspect of the research is found in the third chapter. In this chapter, titled "Speech Verbs in the Syriac Language," there are also two sections. The first section, "Verbal Semantics of Speech in the Syriac Language," revolves around verbs that indicate speech in their secondary meaning in the Syriac language. The second section, "Analytical and Lexical Study of Speech Verbs in the Syriac Language," is the applied section that discusses speech verbs in the Syriac language and compares them with other Semitic languages, providing examples and historical evidence.